Cost of capital analysis in emerging markets: case of a peruvian brewery - Lizarzaburu Bolaños, Edmundo R. (2018)
This paper addresses the calculation of the cost of capital for emerging market companies in the form of a case study. The main objective of this work is to provide a methodology to estimate the Weighted Average Cost of Capital (WACC), applying it to Backus S.A.A., a Peruvian brewery company. The case presents a brief industry description, the company’s background and operations, business and financial strategy and theoretical framework and analyses of the market value of the firm, financial distress, and WACC, assessing each component. Finally, the students are left with the task of calculating WACC and drafting the report.